Full-length transcriptome and long non-coding RNA profiling of whiteleg shrimp Penaeus vannamei hemocytes in response to Spiroplasma eriocheiris infection. Issue 106 (November 2020) - Ren, Yaoqing; Li, Jingyu; Guo, Liang; Liu, Jian Ning; Wan, Hui; Meng, Qingguo; Wang, Hui; Wang, Zisheng; Lv, Linlan; Dong, Xuexing; Zhao, Weihong; Zeng, Qifan; et al.
Abstract: Spiroplasma eriocheiris ( S. eriocheiris ) infection causes a significant economic loss in Penaeus vannamei (P. vannamei) culture industry. However, the response of P. vannamei hemocytes to S. eriocheiris infection has not been extensively studied. In this study, we conducted full-length transcriptome and long non-coding RNA (lncRNA) analyses of P. vannamei hemocytes by a challenge test with S. eriocheiris . Following assembly and annotation, there were 8077 high-quality unigenes. A total of 1168 differentially expressed genes (DEGs) were obtained, including 792 up-regulated and 376 down-regulated genes by differential expression analysis. Gene ontology (GO) enrichment analysis showed that the up-regulated DEGs were mainly clustered into immune system process, defense response, cell cycle and organelle organization. On the other hand, the down-regulated DEGs included that genes that were mainly clustered into metabolic processes related to organic compounds, metabolic process and cellular metabolic process. Protein-protein interaction (PPI) network analysis of DEGs indicated that the pivotal gene interactions were connected to stress response, immune system process and cell cycle. The lncRNA analysis identified multiple lncRNAs, which were highly co-expressed with the immune-related genes, such as lncRNA transcript-12631 and transcript-12631, suggesting that lncRNAs may be involved in the regulation of immune defense in shrimp hemocytes. Additionally, 20 hub unigenes and putative lncRNAs related to immune system were validated by quantitative real-time PCR (qRT-PCR), validating the reliability of RNA-Seq. This study revealed a close connection between the immune and metabolic systems of S. eriocheiris infected P. vannamei . Graphical abstract: Image 1 Highlights: Innate immune responses were the major contributor to protecting P. vannamei against S. eriocheiris infection. Innate immune and metabolic systems intertwined to respond against S. eriocheiris infection in P. vannamei hemocytes. lncRNAs participated in the regulation of immune defense against S. eriocheiris infection in P. vannamei hemocytes.